The impact and value of the Parkinson’s nurse specialist to people with Parkinson’s and their care partners: a grounded theory qualitative study - Kathryn Mcewan; Amanda Clarke; Sonia Dalkin; Annette Hand (BMC Nursing)
Abstract Background Where available, Parkinson’s Nurse Specialists (PNS) provide a range of care, support, guidance, and advocacy for people with Parkinson’s (PwP), and, where appropriate, their care partners (CP). Parkinson’s is a complex and progressive condition. Consequently, evaluating health outcomes is not a reliable method to understand the value and impact of PNS. Previous research has identified PNS can improve the subjective well-being of PwP in the community, also that barriers to care include heavy caseloads and a lack of time. Yet little is known about the value of the role of the PNS, particularly about the impact of pharmacological management and review. This research aims to close this research gap by providing explanatory theories of the impact and value of PNS to PwP, their CP, and other professionals. Methods A social constructivist grounded theory approach was used. Semi-structured interviews were conducted with three groups, PNS, PwP, and CP. Interviews were analysed using NVivo for coding and categorising and Word for memo-writing. Data was analysed inductively and iteratively to identify contexts, social processes, actions, and behaviours, before final emergent theories were identified. Results 46 semi-structured interviews (PNS 18, PwP 19, CP 9) led to four data categories and 13 sub-categories that delineated PNS value. (1) Expert Counsel; provision of emotional support, education, and lifestyle guidance; CP inclusion; provision from diagnosis; and across all stages of Parkinson’s. (2) Conduit of Care; signposting, referral, and connection to PwP, CP, others; PNS barriers and facilitators; (3) Team/Partnership; continuity and partnership, ‘working together’; (4) Pharmacological Support, PNS prescribing; concordance; speed of treatment. Where PNS were accessible they could offer personalised support and partnership, so providing person-centred care that improves health and well-being. Conclusion Where a PNS is accessible due to service availability and manageable caseloads, to provide person-centred care, they deliver several benefits to PwP and CP which improve health and perceived well-being. Where PNS are not available, PwP and CP often struggle to manage their Parkinson’s with negative impacts on health and well-being.